Diagnóstico citopatológico de afecções mamárias em cadelas: revisão - Colodel, Márcia Moleta [UNESP]; Ramos, Renata dos Santos [UNESP]; Rocha, Noeme Sousa [UNESP] (My University, 2010)
Mammary affection in bitches is a routine finding in small animal clinic. The use cytopathological examination as a means to obtain mammary lesion diagnosis in the last decades in Veterinary Medicine. The advantages of this examination are: it is fast, cheap, effective, simple and little invasive. The mammary samples for cytopathology exam may be obtained from glandular secretion or more commonly via fi ne needle cytology that may be performed with or without aspiration. In order to obtain relevant clinical results, it is important to get good samples and have good knowledge of cell morphology and cell disposition. Despite lowing inconclusive results, the cytopathology allows to distinguish neoplastic lesions from infl ammatory, hyperplasic or degenerative. It can also help in the identifi cation of infectant agents and guide a fast and appropriate therapy. Therefore it can be used to diagnose mammary conditions. The objective of this study is to encourage veterinarians to insert the cytopathology examination in the array of auxiliary tests for mammary lesions in bitches.

As afecções mamárias em cadelas são encontradas rotineiramente na clínica de pequenos animais. O uso do exame citopatológico como meio diagnóstico nas lesões mamárias vem crescendo nas últimas décadas na Medicina Veterinária. As vantagens desse exame estão relacionadas à rapidez, ao baixo custo, efi cácia, simplicidade e ao fato de ser pouco invasivo. As amostras mamárias destinadas ao exame citopatológico podem ser obtidas através da secreção glandular ou, mais comumente, por citologia por punção com ou sem aspiração. Para a obtenção de resultados clinicamente relevantes, é fundamental a obtenção de boas amostras e a interpretação básica da morfologia e da disposição detalhada de cada célula. Em virtude disso, ainda que o resultado seja inconclusivo, a citopatologia permite distinguir lesões neoplásicas de infl amatórias, hiperplásicas e degenerativas, além de auxiliar na identifi cação de agentes infecciosos e direcionar a uma conduta terapêutica e prognóstica mais rápida e adequada, portanto deve ser usada para diagnosticar afecções mamárias. O presente trabalho tem por objetivo incentivar os profi ssionais médicos veterinários a inserir na lista de auxílios diagnósticos de lesões de mama de cadela o exame citopatológico.
Cytopathologic diagnosis of mammary affections in bitches: review
Keywords: Mammary gland; Female dog; Diagnosis; Cytopathology; Mama; Cadela; Diagnóstico; Citopatologia